The Impact of Squat Depth Jump and Up-Down Bench Exercises on Jump Distance - Addriana Bulu Baan; Didik Purwanto; Arief Aditya Rifandy; Hendrik Mentara (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The study examines the impact of squad depth jump training and up-and down-the-bench training on an individual's jumping ability. Its objective is to determine whether these specific training regimens contribute to an increase in the distance a person can jump. Materials and Methods. The study consisted of a population of 40 students, and the sampling technique applied was purposive sampling. Data collection involved the use of test techniques, specifically the squad depth jump and up-down bench tests. Results. After conducting an analysis using descriptive statistical techniques, we found that for the training ability test, the calculated T value is 3.162, while the critical T value from the T table is 2.093. This indicates that the calculated T value exceeds the critical T value, as 3.162 is greater than 2.093. Conclusion. After undergoing squad depth jump training and up-down-the-bench training, the student demonstrated notable enhancement in their athletic abilities, particularly in jump distance. These results provide strong evidence in support of the hypothesis that these particular training methods have a positive and impactful influence on jump performance.